Hubungan prematuritas dengan kejadian sepsis neonatorum yang dirawat di ruang perinatologi dan neonatal intensive care unit (NICU) RSUD Wangaya kota Denpasar - I Gusti Amanda Jaya; I Wayan Bikin Suryawan; Putu Pramitha Rahayu (Intisari Sains Medis, 2019)
Background: Premature neonates have an immature immune system due to the lack of IgG antibodies. These antibodies do not cross the placenta from mother to baby at last trimester that can increase the risk of neonatal sepsis. This study aims to determine the relationship between prematurity and the incidence of neonatal sepsis at Perinatology Ward and NICU Wangaya General Hospitals, Denpasar.Methods: This research used analytical observation with cross sectional study design from January-April 2018. The samples involved are 50 neonates, admitted at Perinatology Ward and NICU Wangaya Hospital and fulfilled the inclusion and exclusion criteria. Samples were obtained by using consecutive sampling method and using secondary data from the medical recordResult: 23 samples (46%) premature and 27 samples (54%) were not premature, out of 50 samples as many as 20 samples with neonatal sepsis. From the results of hypothesis testing using the chi-square test, the p-value is 0.005, and the prevalence risk was 2.73.Conclusion: Prematurity is significantly related with the incident of neonatal sepsis at Perinatology Ward and NICU Wangaya Hospital, Denpasar City.